Archaeological trial excavations in the basement of Silvije Strahimir Kranjčević Elementary School in Senj (In situ, 2024)
During February 2023, archaeological trial excavations were conducted at the Štela site in Senj, in the basement of Silvije Strahimir Kranjčević Elementary School. The excavation consisted of documenting the Roman-erawater reservoir SB2 discovered during the construction of the elementary school in 1972, and trial excavation carried out on part of the floor of the water reservoir. The main goal of this research was to document the water reservoir using more modern documentation techniques and to open a trial trench under the water reservoir in order to determine the technique and the chronological framework of the construction. The research showed the existence of at least two phases of the water reservoir.
Keywords: Senia; antiquity; water reservoir; archaeological trial excavations